2006
DOI: 10.1016/j.bbamem.2006.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Functional and molecular characterization of adenosine transport at the rat inner blood–retinal barrier

Abstract: The purpose of the present study was to characterize the adenosine transport system(s) at the inner blood-retinal barrier (inner BRB). A conditionally immortalized rat retinal capillary endothelial cell line (TR-iBRB2), used as an in vitro model of the inner BRB, expresses equilibrative nucleoside transporter 1 (ENT1), ENT2, concentrative nucleoside transporter 2 (CNT2), and CNT3 mRNAs. TR-iBRB2 cells exhibited an Na+-independent and concentration-dependent [3H]adenosine uptake with a Michaelis-Menten constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 30 publications
7
39
0
Order By: Relevance
“…The temperature-sensitive rat TR-iBRB2 were grown as previously described (Hosoya and Tomi, 2005;Nagase et al, 2006). TR-iBRB2 (denotes transgenic-inner blood-retinal barrier EC line 2) differentiates at 378C, but becomes conditionally immortalized at 338C.…”
Section: Cell Culturementioning
confidence: 99%
“…The temperature-sensitive rat TR-iBRB2 were grown as previously described (Hosoya and Tomi, 2005;Nagase et al, 2006). TR-iBRB2 (denotes transgenic-inner blood-retinal barrier EC line 2) differentiates at 378C, but becomes conditionally immortalized at 338C.…”
Section: Cell Culturementioning
confidence: 99%
“…1B), and K in,brain of [ 3 H]L-ornithine was 11.5 6 0.8 lL/(minÁg brain), which was 1.64-fold lower than the K in,retina and 8.27-fold greater than that of [ 3 H]D-mannitol (1.39 lL/(minÁg brain)). 16 The RUI of [ 3 H]L-ornithine was estimated as 128%, which was much higher than that of [ 3 H]Dmannitol (11.6%) ( Table 1), 39 supporting the blood-to-retina transport of L-ornithine across the BRB. The retinal uptake of [ 3 H]L-ornithine was significantly inhibited by 10 mM Lornithine and 10 mM L-arginine during no inhibition shown by 10 mM L-leucine ( Table 1).…”
Section: In Vitro Transport Analysismentioning
confidence: 93%
“…[8][9][10][11] These pieces of evidence indicate the relevance of Lornithine to health maintenance and pathogeneses, and suggest the physiological importance of regulation of the L-ornithine concentration in the retina where the blood-retinal barrier (BRB) is formed by retinal capillary endothelial cells (inner BRB) and RPE cells (outer BRB) to separate the neural retina and the circulating blood. [12][13][14][15] At the BRB, these responsible cells form tight junctions to restrict paracellular solute transport, 12,13 and previous studies have suggested that the retinal capillary endothelial cells express various transporters, such as equilibrative nucleoside transporter 2 (ENT2/SLC29A2), taurine transporter (TAUT/SLC6A6), L (leucine-referring)-type amino acid transporter (LAT1/SLC7A5) and glucose transporter (GLUT1/SLC2A1), involved in the blood-to-retina transport of nutrients across the inner BRB nourishing two-thirds of the retina, [14][15][16][17][18][19] suggesting the involvement of transporters at the inner BRB in regulating the L-ornithine concentration in the retina.…”
mentioning
confidence: 99%
“…Furthermore, adenosine effects in retina may be regulated by equilibrative (ENT1 and ENT2) and concentrative nucleoside transporters (CNT2 and CNT3) as well as adenosine deaminase 2 (ADA2) (Akanuma et al, 2013;dos Santos-Rodrigues et al, 2011;Elsherbiny et al, 2013;Nagase et al, 2006). In fact, patients with diabetes express a high level of ADA2, which impaired the antiinflammatory activity of adenosine at retina level (Elsherbiny et al, 2013).…”
Section: Presence In Other Posterior Structuresmentioning
confidence: 99%